Sixth cranial nerve palsy in giant cell arteritis: A systematic review - Haruki Sawada,; Yoshito Nishimura,; Hiromichi Tamaki, (Archives of Rheumatology, 2024)
Objectives: This study aimed to review and describe isolated sixth cranial nerve or abducens nerve palsy that may present with subtle ophthalmoplegia in patients with giant cell arteritis (GCA). Materials and methods: In this systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) Extension for Scoping Reviews, MEDLINE and EMBASE were searched for all peer-reviewed articles using the keywords “cranial nerve six,” “abducens nerve,” and “giant cell arteritis” from their inception to December 22, 2022. Results: Twenty-five articles, including seven observational studies and 18 cases, were included. While the incidence and prevalence of sixth nerve palsy in GCA were variable, up to 48% of diplopia in GCA were attributed to the sixth cranial nerve palsy, according to the observational studies included. While 88.2% had a resolution of symptoms with 40-50 mg/day of prednisone-equivalent corticosteroids, it took a median of 24.5 days until the resolution of symptoms from the initiation of treatment. Conclusion: This review summarizes the current understanding of the characteristics of sixth nerve palsy in GCA. While most patients may have reversible clinical courses, a few can suffer from persistent ophthalmoplegia, which is a potentially missed yet crucial clinical finding in GCA. Increased awareness of the sixth nerve palsy in GCA is crucial.